High-oxidation-resistance AlON composite ceramic material and preparation method thereof
By mixing Al2O3 and AlN powder with boride and silicide powder and sintering using SPS technology, AlON composite ceramics with excellent oxidation resistance were prepared, which solved the problem of oxidation reaction of AlON ceramics in high-temperature environments and significantly improved its anti-oxidation and mechanical properties.
Patent Information
- Application Number
- CN202411903568.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-03-28
AI Technical Summary
AlON ceramics are prone to oxidation reactions in high-temperature oxygen-containing environments, resulting in reduced mechanical strength and deterioration of material surfaces, limiting their service life and stability.
AlON composite ceramics with excellent oxidation resistance were prepared by mixing Al2O3 and AlN powder with boride and silicide powder and sintering by discharge plasma sintering (SPS) technology.
It significantly improves the oxidation resistance and mechanical properties of AlON composite ceramics, extends its service life, and can better meet the needs of high-performance and high-temperature resistant materials in the fields of aerospace, energy and electronic devices.
Smart Images

Figure CN119707500A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a high-oxidation-resistance AlON composite ceramic material and a preparation method thereof, belonging to the field of ceramic material preparation. Background Art
[0002] Aluminum oxynitride (AlON) ceramics are a new type of functional material composed of aluminum, oxygen and nitrogen in a non-stoichiometric ratio. They have high strength, high hardness, excellent wear resistance and scratch resistance, and show great application potential in aerospace, automotive industry, police explosion protection, electronic devices and other fields. Although AlON ceramics have excellent mechanical properties, they are very susceptible to oxidation reactions in high-temperature oxygen-containing environments. The oxidation chemical equation is 4AlON+3O2=2Al2O3+N2. This oxidation process will not only reduce the mechanical strength of AlON ceramics, but may also cause degradation of the material surface, seriously affecting its long-term performance. Therefore, the anti-oxidation property of AlON ceramics has become one of the key factors limiting its service life and stability.
[0003] At present, the common method for improving the oxidation resistance of ceramic materials is the coating method. Patent CN118063192A discloses a method for preparing a high-temperature antioxidant glass coating of nitride ceramics. The method uses mullite powder and glass powder as the main raw materials to prepare a slurry, and applies it on the surface of the nitride ceramic substrate, and forms a glass coating after pre-curing and sintering, thereby providing oxidation protection for the substrate material. Patent CN118290174A proposes a method for improving the oxidation resistance of carbon fiber reinforced ceramic matrix composites. The method enhances the interface bonding strength between carbon fiber and ceramic matrix by means of surface pretreatment, modification technology and control of curing conditions, and uses vapor deposition technology to coat an antioxidant layer on the surface of the material, thereby effectively preventing oxygen from invading and improving the oxidation resistance of the composite material. Patent CN118324555A proposes a method for preparing a high-temperature antioxidant protective coating of nitride ceramics. The method uses silane coupling agent and borate ester for coating treatment, forms a diaphragm structure by heating curing and heat treatment, and effectively improves the high-temperature oxidation resistance of nitride ceramics. Although the above coating technology has improved the antioxidant properties of ceramic materials to a certain extent, there are still some obvious limitations. First, the uniformity and density of the coating are difficult to fully control, and it is easy to have tiny defects or cracks, which weaken the antioxidant effect. Secondly, due to the possible difference in thermal expansion coefficient between the coating material and the substrate, the coating is prone to peeling or cracking in a high temperature environment. In addition, the complexity and multi-step operation of the coating technology not only increase the production cost, but also increase the process difficulty.
[0004] In view of the above problems, it is particularly important to develop new methods to improve the oxidation resistance of AlON ceramics. By optimizing the bulk structure of the material or introducing an oxidation-resistant second phase structure, the limitations of existing coating technology can be overcome and the oxidation resistance of the material can be fundamentally improved to better meet the stringent requirements of modern industry for high-temperature materials. Summary of the invention
[0005] The present invention aims to provide a highly antioxidant AlON composite ceramic material and a preparation method thereof, so as to solve the problem that the existing AlON ceramics have insufficient antioxidant properties in high temperature environments. By mixing Al2O3 and AlN powders with at least one boride and one silicide powder, and sintering them using spark plasma sintering (SPS) technology, AlON composite ceramics with excellent antioxidant properties are successfully prepared. By precisely controlling the type and content of the second phase, while optimizing the microstructure of the composite ceramic and significantly improving the antioxidant properties of the material, its mechanical properties are further improved, so that the material can better meet the stringent requirements for high-performance, high-temperature resistant materials in the fields of aerospace, energy, and electronic devices.
[0006] The present invention provides a method for preparing a highly oxidation-resistant AlON composite ceramic material, which mainly comprises the following steps:
[0007] Step 1) Using Al2O3 and AlN powder as raw materials, at least one boride and one silicide powder are added as the second phase material. The purity of Al2O3 and AlN powder is greater than 99%, and the mass ratio of the two is 7:3 to 9:1; the boride is selected from one or more of TiB2, ZrB2, WB, MoB2, and CrB2; the silicide is selected from one or more of TiSi2, ZrSi2, WSi2, MoSi2, and CrSi2; the particle size of the boride and silicide is less than 5μm, the purity is greater than 99%, and the total doping amount is 1 to 10% of the total mass of the Al2O3 and AlN powders.
[0008] Step 2) The powder is ball-milled using an omnidirectional planetary ball mill, the ball-milling time is 5 to 30 hours, and the ball-milling speed is 100 to 300 r / min.
[0009] Step 3) Dry the ball-milled mixed powder using a rotary evaporator, and sieve the dried powder.
[0010] Step 4) The sieved mixed powder is loaded into a carbon fiber mold, and the powder is densified and sintered using SPS technology to obtain AlON composite ceramics. The specific sintering process is: heating rate 50-150°C / min, sintering pressure 20-80MPa, sintering temperature 1600°C-1700°C, and holding time 1-10min.
[0011] The AlON composite ceramic prepared according to the preparation method of the high oxidation resistance AlON composite ceramic material has a hardness greater than 17GPa, a bending strength greater than 300MPa, and a fracture toughness greater than 4.5MPa·m 1 / 2 .
[0012] The beneficial effects of the present invention include:
[0013] 1) In a high-temperature oxidizing environment, the second phase materials such as borides and silicides in AlON composite ceramics can react with oxygen to form a dense oxide protective layer on the ceramic surface. For example, borides such as TiB2, ZrB2, WB, MoB2, CrB2 react with oxygen to form corresponding metal oxides and B2O3; silicides such as TiSi2, ZrSi2, WSi2, MoSi2, CrSi2 react with oxygen to form corresponding metal oxides and SiO2. These oxides have extremely low oxygen permeability and can remain stable at high temperatures without significant volatilization or decomposition, thereby effectively preventing oxygen from penetrating into the matrix. In addition, at high temperatures, part of B2O3 can react with a small amount of Al2O3 generated by oxidation of SiO2 or AlON ceramics to form a borosilicate (B2O3·nSiO2) or aluminum borate (Al2O3·nB2O3) glassy layer, which greatly reduces the probability of direct contact between oxygen and the matrix material and significantly slows down the oxidation rate of AlON ceramic materials.
[0014] 2) During the preparation of AlON composite ceramics, the solid-phase reaction between Al2O3 and AlN powder significantly promotes the diffusion and mass transfer between powder particles, so that second-phase particles such as borides and silicides can effectively diffuse and evenly distribute in the generated AlON matrix. This process not only helps to fill the micropores and defects in the material, and reduce the existence of microcracks and pores that may become oxygen channels, but also ensures that the oxide layer formed by the second-phase particles and the AlON matrix has a high bonding strength during the high-temperature oxidation process by enhancing the interfacial bonding between the second-phase particles and the AlON matrix. This mechanism effectively prevents the occurrence of interfacial cracks or delamination between the oxide layer and the matrix, thereby preventing the diffusion of oxygen into the matrix, and significantly improving the material's antioxidant properties. In addition, the uniform distribution of the second-phase material can also refine the grains and produce a particle strengthening effect, further improving the mechanical properties of the composite ceramics. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 is the thickness of the oxide layer of the pure AlON ceramic after oxidation treatment in Comparative Example 1;
[0016] Figure 2 is the thickness of the oxide layer of the AlON composite ceramic after oxidation treatment in Example 1;
[0017] Figure 3 is the thickness of the oxide layer of the pure AlON ceramic after oxidation treatment in Comparative Example 2;
[0018] Figure 4 is the thickness of the oxide layer of the AlON composite ceramic after oxidation treatment in Example 2;
[0019] Figure 5 is the thickness of the oxide layer of the pure AlON ceramic after oxidation treatment in Comparative Example 3;
[0020] Figure 6 is the thickness of the oxide layer of the AlON composite ceramic after oxidation treatment in Example 3. DETAILED DESCRIPTION
[0021] The present invention is further described below with reference to the accompanying drawings and specific embodiments, but they are not intended to limit the present invention.
[0022] Comparative Example 1
[0023] Step 1) Using Al2O3 (purity 99.99%) and AlN (purity 99.9%) powders in a mass ratio of 7:3 as raw materials.
[0024] Step 2) The raw material powder is ball-milled using an omnidirectional planetary ball mill, the ball-milling time is 20 h, and the ball-milling speed is 100 r / min.
[0025] Step 3) The ball-milled powder is dried using a rotary evaporator and then sieved to remove agglomerates in the powder.
[0026] Step 4) The sieved mixed powder is loaded into a carbon fiber mold, and the powder is densified and sintered using SPS technology to prepare pure AlON ceramics. The specific sintering process is: heating rate 100°C / min, sintering pressure 50MPa, sintering temperature 1650°C, and holding time 5min.
[0027] The mechanical properties test showed that the hardness of the pure AlON ceramic was 14.33 GPa, the bending strength was 163 MPa, and the fracture toughness was 3.18 MPa·m 1 / 2 Subsequently, the ceramic was placed in a muffle furnace and subjected to high-temperature oxidation treatment in air at a temperature of 1250°C for 40 hours. After oxidation treatment, the thickness of the oxide layer formed on the surface of the material was about 150 μm. Figure 1 shown.
[0028] Example 1
[0029] Step 1) Using Al2O3 (purity 99.99%) and AlN (purity 99.9%) powders in a mass ratio of 7:3 as raw materials, TiB2 (purity 99.9%) and ZrSi2 (purity 99.5%) are added as second phase materials. The particle size of TiB2 is about 2 μm, the particle size of ZrSi2 is about 1 μm, and the total doping amount of the two is 1% of the total mass of Al2O3 and AlN powders.
[0030] Step 2) is the same as that of Comparative Example 1.
[0031] Step 3) is the same as that of Comparative Example 1.
[0032] Step 4) The sieved mixed powder is loaded into a carbon fiber mold, and the powder is densified and sintered using SPS technology to prepare AlON composite ceramics. The specific sintering process is: heating rate 100°C / min, sintering pressure 50MPa, sintering temperature 1650°C, and holding time 5min.
[0033] The mechanical properties test showed that the hardness of the AlON composite ceramic was 17.03 GPa, the bending strength was 330 MPa, and the fracture toughness was 5.45 MPa·m 1 / 2 Subsequently, the ceramic was placed in a muffle furnace and subjected to high-temperature oxidation treatment in air at a temperature of 1250°C for 40 hours. After oxidation treatment, the thickness of the oxide layer formed on the surface of the material was about 69 μm. Figure 2 Compared with the pure AlON ceramic prepared by the same process in Comparative Example 1, the mechanical properties of the AlON composite ceramic are significantly improved, and after oxidation treatment, the thickness of its oxide layer is reduced by about 54%. This result shows that the AlON composite ceramic has a significant advantage in oxidation resistance.
[0034] Comparative Example 2
[0035] Step 1) Using Al2O3 (purity 99.99%) and AlN (purity 99.9%) powders in a mass ratio of 8:2 as raw materials.
[0036] Step 2) The powder was milled using a planetary ball mill for 5 h at a speed of 300 r / min.
[0037] Step 3) is the same as that of Comparative Example 1.
[0038] Step 4) The sieved mixed powder is loaded into a carbon fiber mold, and the powder is densified and sintered using SPS technology to prepare pure AlON ceramics. The specific sintering process is: heating rate 50°C / min, sintering pressure 20MPa, sintering temperature 1700°C, and holding time 1min.
[0039] The mechanical properties test showed that the hardness of the pure AlON ceramic was 13.04 GPa, the bending strength was 124 MPa, and the fracture toughness was 3.52 MPa·m 1 / 2 Subsequently, the ceramic was placed in a muffle furnace and subjected to high-temperature oxidation treatment in air at a temperature of 1250°C for 40 hours. After oxidation treatment, the thickness of the oxide layer formed on the surface of the material was about 90 μm. Figure 3 shown.
[0040] Example 2
[0041] Step 1) Using Al2O3 (purity 99.99%) and AlN (purity 99.9%) powders with a mass ratio of 8:2 as raw materials, WB (purity 99.5%) and CrSi2 (purity 99.9%) are added as second phase materials. The particle size of WB is about 2 μm, the particle size of CrSi2 is about 4 μm, and the total doping amount of the two is 5% of the total mass of Al2O3 and AlN powders.
[0042] Step 2) is the same as Comparative Example 2.
[0043] Step 3) is the same as that of Comparative Example 1.
[0044] Step 4) The sieved mixed powder is loaded into a carbon fiber mold, and the powder is densified and sintered using SPS technology to prepare AlON composite ceramics. The specific sintering process is: heating rate 50°C / min, sintering pressure 20MPa, sintering temperature 1700°C, and holding time 1min.
[0045] The mechanical properties test showed that the hardness of the AlON composite ceramic was 17.81 GPa, the bending strength was 505 MPa, and the fracture toughness was 4.80 MPa·m 1 / 2 Subsequently, the ceramic was placed in a muffle furnace and subjected to high-temperature oxidation treatment in air at a temperature of 1250°C for 40 hours. After oxidation treatment, the thickness of the oxide layer formed on the surface of the material was about 43 μm. Figure 4 Compared with the pure AlON ceramic prepared by the same process in Comparative Example 2, the mechanical properties of the AlON composite ceramic are significantly improved, and after oxidation treatment, the thickness of its oxide layer is reduced by about 52%. This result shows that the AlON composite ceramic has a significant advantage in oxidation resistance.
[0046] Comparative Example 3
[0047] Step 1) Using Al2O3 (purity 99.99%) and AlN (purity 99.9%) powders in a mass ratio of 9:1 as raw materials.
[0048] Step 2) The powder was milled using a planetary ball mill for 30 h at a speed of 200 r / min.
[0049] Step 3) is the same as that of Comparative Example 1.
[0050] Step 4) The sieved mixed powder is loaded into a carbon fiber mold, and the powder is densified and sintered using SPS technology to prepare pure AlON ceramics. The specific sintering process is: heating rate 150°C / min, sintering pressure 80MPa, sintering temperature 1600°C, and holding time 10min.
[0051] The mechanical properties test showed that the hardness of the pure AlON ceramic was 13.75 GPa, the bending strength was 177 MPa, and the fracture toughness was 2.86 MPa·m 1 / 2 Subsequently, the ceramic was placed in a muffle furnace and subjected to high-temperature oxidation treatment in air at a temperature of 1250°C for 40 hours. After oxidation treatment, the thickness of the oxide layer formed on the surface of the material was about 122 μm. Figure 5 shown.
[0052] Example 3
[0053] Step 1) Using Al2O3 (purity 99.99%) and AlN (purity 99.9%) powders in a mass ratio of 9:1 as raw materials, ZrB2 (purity 99.5%) and TiSi2 (purity 99.5%) are added as second phase materials. The particle size of ZrB2 is about 3 μm, the particle size of TiSi2 is about 2 μm, and the total doping amount of the two is 10% of the total mass of Al2O3 and AlN powders.
[0054] Step 2) is the same as Comparative Example 3.
[0055] Step 3) is the same as that of Comparative Example 1.
[0056] Step 4) The sieved mixed powder is loaded into a carbon fiber mold, and the powder is densified and sintered using SPS technology to prepare AlON composite ceramics. The specific sintering process is: heating rate 150°C / min, sintering pressure 80MPa, sintering temperature 1600°C, and holding time 10min.
[0057] The mechanical properties test showed that the AlON composite ceramic had a hardness of 18.21 GPa, a bending strength of 479 MPa, and a fracture toughness of 4.97 MPa·m 1 / 2 Subsequently, the ceramic was placed in a muffle furnace and subjected to high-temperature oxidation treatment in air at a temperature of 1250°C for 40 hours. After oxidation treatment, the thickness of the oxide layer formed on the surface of the material was about 40 μm. Figure 6Compared with the pure AlON ceramic prepared by the same process in Comparative Example 3, the mechanical properties of the AlON composite ceramic are significantly improved, and after oxidation treatment, the thickness of its oxide layer is reduced by about 67%. This result shows that the AlON composite ceramic has a significant advantage in oxidation resistance.
[0058] The above content illustrates the embodiments of the present invention in conjunction with the accompanying drawings, but the present invention includes but is not limited to the above embodiments. Any modification, supplement, equivalent replacement or partial improvement made under the principle of the spirit of the present invention shall be deemed to be within the protection scope of the present invention.
Claims
1. A method for preparing a highly oxidation-resistant AlON composite ceramic material, characterized in that: The method comprises the following steps: 1) Using aluminum oxide (Al2O3) and aluminum nitride (AlN) powder as raw materials, adding at least one boride and one silicide powder as second phase materials; 2) ball milling the above powder to ensure that the raw materials are fully mixed and uniformly refined; 3) Drying and sieving the mixed powder; 4) The sieved mixed powder is placed in a mold and subjected to spark plasma sintering to prepare AlON composite ceramics.
2. The method for preparing a highly oxidation-resistant AlON composite ceramic material according to claim 1, characterized in that: In the step 1), the purity of Al2O3 and AlN powders is greater than 99%, and the mass ratio of the two is 7:3 to 9:
1.
3. The method for preparing a highly oxidation-resistant AlON composite ceramic material according to claim 1, characterized in that: In the step 1), the boride is selected from one or more of titanium diboride (TiB2), zirconium diboride (ZrB2), tungsten boride (WB), molybdenum diboride (MoB2), and chromium diboride (CrB2); the silicide is selected from one or more of titanium disilicide (TiSi2), zirconium disilicide (ZrSi2), tungsten disilicide (WSi2), molybdenum disilicide (MoSi2), and chromium disilicide (CrSi2).
4. The method for preparing a highly oxidation-resistant AlON composite ceramic material according to claim 1, characterized in that: In the step 1), the particle size of the boride and the silicide is less than 5 μm, and the purity is greater than 99%.
5. The method for preparing a highly oxidation-resistant AlON composite ceramic material according to claim 1, characterized in that: In the step 1), the total doping amount of the boride and the silicide is 1-10% of the total mass of the Al2O3 and AlN powders.
6. The method for preparing a highly oxidation-resistant AlON composite ceramic material according to claim 1, characterized in that: In the step 2), the ball milling time is 5 to 30 hours, and the ball milling speed is 100 to 300 r / min.
7. The method for preparing a highly oxidation-resistant AlON composite ceramic material according to claim 1, characterized in that: In the step 4), the spark plasma sintering process is: a heating rate of 50 to 150° C. / min, a sintering pressure of 20 to 80 MPa, a sintering temperature of 1600 to 1700° C., and a holding time of 1 to 10 min.
8. A highly oxidation-resistant AlON composite ceramic obtained by the preparation method according to any one of claims 1 to 7.
Citation Information
Patent Citations
Nitrogen oxide transparent ceramic high-temperature anti-oxidation glass coating and preparation method thereof
CN118063192A
Method for improving oxidation resistance of carbon fiber reinforced ceramic-based composite material
CN118290174A
High-temperature anti-oxidation protective coating material for nitride ceramics as well as preparation method and application of high-temperature anti-oxidation protective coating material
CN118324555A